Pridobivanje in uporaba ekstraktivov iz lesa in drevesne skorje - Oven, Primož (Gozdarski vestnik, 2024)
Extractives are low molecular weight compounds found in all plant tissues, including wood and tree bark. They have important ecological and physiological functions in trees, and at the same time, they represent bio-based products with high added value, which can also be obtained from wood of lower quality and biomass residues of forestry-wood chains. In this paper, we will classify extractives, explain the qualitative and quantitative variability in individual tissues of the selected tree species, and present the methods of extraction and areas of application. We estimate that the production of extractives is a fairly simple technological process that would be feasible in the form of a small biorefinery in rural environments where sufficient amounts of wood biomass are available.
Keywords: bark; biorafinacija; biorefining; cascade use; ekstraktivi; extractives; kaskadna raba; les; skorja; wood